2014
DOI: 10.1186/1759-8753-5-4
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal transfer of transposons between and within crustaceans and insects

Abstract: BackgroundHorizontal transfer of transposable elements (HTT) is increasingly appreciated as an important source of genome and species evolution in eukaryotes. However, our understanding of HTT dynamics is still poor in eukaryotes because the diversity of species for which whole genome sequences are available is biased and does not reflect the global eukaryote diversity.ResultsIn this study we characterized two Mariner transposable elements (TEs) in the genome of several terrestrial crustacean isopods, a group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…This unprecedented figure is more than four times higher than the total number of HTT events reported so far in metazoans, plants, and fungi combined (10). Such a high number is still not unexpected, given that studies focusing on one or a few TEs often found one or more HTT events between multiple, distantly related taxa (11,(14)(15)(16)22).…”
Section: Significancementioning
confidence: 66%
See 1 more Smart Citation
“…This unprecedented figure is more than four times higher than the total number of HTT events reported so far in metazoans, plants, and fungi combined (10). Such a high number is still not unexpected, given that studies focusing on one or a few TEs often found one or more HTT events between multiple, distantly related taxa (11,(14)(15)(16)22).…”
Section: Significancementioning
confidence: 66%
“…HT of TEs (HTT) may allow these elements to enter naive genomes, which they invade by making copies of themselves, and then escape before they become fully silenced by anti-TE defenses (13). A growing number of studies have identified such HTT (11,[14][15][16]. However, a common drawback of these studies has been the inclusion of a limited set of TEs (11) or organisms (16), which hampers our understanding of the breadth of HTT, its contribution to genome evolution, and of the factors and barriers shaping these transfers in eukaryotes (13).…”
mentioning
confidence: 99%
“…Yamada et al (2014) evidenced the occurrence of HTTs of a Mariner-like element between a bee, a wasp and a butterfly in the south-west islands of Japan. Dupeyron et al (2014) identified HTTs between crustacean (terrestrial isopods) and insects. They used a combination of in silico and wet laboratory approaches to evidence multiple transfers of two Mariner transposon families Crmar2 and Mariner-5-Dbi.…”
Section: Detection Of Htts From Full Genome Sequencesmentioning
confidence: 97%
“…Here, consider the same effect in a model with a finite population of size N . We use a previously published model of horizontal gene transfer 48 which is easily generalized to other mechanisms of horizontal transmission of genetic elements found in multicellular organisms such as crustaceans and insects 49 . This model ( (7)) distinguishes the effects of the transmission rate β of the bene and the selective value s of the bene.…”
Section: Supplementary Informationmentioning
confidence: 99%